Reinforcement Learning for Spoken Dialogue Systems: Comparing Strengths and Weaknesses for Practical Deployment - Paek, Tim (2006)
In a spoken dialogue system, the function of a dialogue manager is to select actions based on observed events and inferred beliefs. To formalize and optimize the action selection process, researchers have turned to reinforcement learning methods which represent the dynamics of a spoken dialogue as a fully or partially observable Markov Decision Process. Once represented as such, optimal policies prescribing what actions the system should take in order to maximize a reward function can be learned from data. Formerly, this task was assigned to the application developer, who typically hand-crafted rules or heuristics. In this position paper, we assess to what extent the action selection process can be automated by current state-of-the-art reinforcement learning methods for dialogue management. In examining the strengths and weaknesses of these methods with respect to practical deployment, we discuss the challenges that need to be overcome before these methods can become commonplace in deployed systems.